ASSESSING TEACHERS’ READINESS AND CHALLENGES IN IMPLEMENTING MOBILE-ASSISTED LANGUAGE LEARNING (MALL) IN RURAL AREAS - Opirman Waruwu (Universitas Nias Raya, 2026)
This study seeks to investigate the readiness of English teachers and the obstacles they face in adopting Mobile-Assisted Language Learning (MALL) in rural areas of Mandrehe Utara Sub-district, West Nias Regency, North Sumatra. Using a qualitative research design grounded in a phenomenological approach, data were collected through semi-structured in-depth interviews, non-participant classroom observations, and document analysis involving eight English teachers from five different schools. The results indicate that teachers’ readiness falls within low to moderate levels. While attitudinal readiness appears relatively favourable, both knowledge-based and practical readiness remain notably limited. The study further identifies four major challenges: inadequate technological infrastructure, limited digital literacy among teachers, a lack of sufficient institutional support, and pedagogical issues related to classroom management. Based on these findings, the study suggests the need to prioritise the improvement of digital infrastructure, provide context-sensitive professional development, and formulate school policies that clearly encourage the integration of mobile technology into English language instruction in remote rural contexts.